Near-infrared fluorescence imaging of experimentally collagen-induced arthritis in rats using the nonspecific dye tetrasulfocyanine in comparison with gadolinium-based contrast-enhanced magnetic resonance imaging, histology, and clinical score - Gemeinhardt, Ines; Puls, Dorothee; Gemeinhardt, Ole; Taupitz, Matthias; Wagner, Susanne; Schnorr, Beatrix; Licha, Kai; Schirner, Michael; Ebert, Bernd; Petzelt, Diethard; Macdonald, Rainer; Schnorr, Jörg (Journal of biomedical optics, 2012)
Using 15 rats with collagen-induced arthritis (30 joints) and 7 control rats (14 joints), we correlated the intensity of near-infrared fluorescence (NIRF) of the nonspecific dye tetrasulfocyanine (TSC) with magnetic resonance imaging (MRI), histopathology, and clinical score. Fluorescence images were obtained in reflection geometry using a NIRF camera system. Normalized fluorescence intensity (INF) was determined after intravenous dye administration on different time points up to 120 min. Contrast-enhanced MRI using gadodiamide was performed after NIRF imaging. Analyses were performed in a blinded fashion. Histopathological and clinical scores were determined for each ankle joint. INF of moderate and high-grade arthritic joints were significantly higher (p<0.005) than the values of control and low-grade arthritic joints between 5 and 30 min after TSC-injection. This result correlated well with post-contrast MRI signal intensities at about 5 min after gadodiamide administration. Furthermore, INF and signal increase on contrast-enhanced MRI showed high correlation with clinical and histopathological scores. Sensitivities and specificities for detection of moderate and high-grade arthritic joints were slightly lower for NIRF imaging (89%/81%) than for MRI (100%/91%). NIRF imaging using TSC, which is characterized by slower plasma clearance compared to indocyanine green (ICG), has the potential to improve monitoring of inflamed joints.